Towards sustainable fisheries of the Oresund cod (Gadus morhua) through sub-stock-specific assessment and management recommendations - Lindegren, Martin; Waldo, Staffan; Nilsson, P. Anders; Svedäng, Henrik; Persson, Anders (ICES Journal of Marine Science, 2013)
<qd> Lindegren, M., Waldo, S., Nilsson, P. A., Svedäng, H., and Persson, A. Towards sustainable fisheries of the Öresund cod ( Gadus morhua ) through sub-stock-specific assessment and management recommendations. – ICES Journal of Marine Science, doi.10.1093/icesjms/fst042. </qd>Fisheries management traditionally relies on stock assessments assuming discrete populations within large administrational areas. However, failing to account for sub-stock structuring may result in overestimation of the stocks' true harvest potential and unsustainable exploitation of small stock elements. Atlantic cod ( Gadus morhua ) frequently occurs in spatially segregated populations, some of which exhibit fine-scaled stock structuring within current management boundaries. Here we use the locally spawning cod stock in the Sound (“Öresund”) as a case study, and perform a sub-stock-specific assessment to evaluate biological and economic effects of managing the Sound cod as a separate stock. Our results indicate that reducing exploitation pressure, particularly through technical regulations i.e. increasing gill-net mesh sizes, would not only enhance the stock age distribution, but yield long-term net benefits to the local gill-net fishery. Furthermore, our study emphasizes the need for developing sub-stock-specific management recommendations in order to ensure the maintenance of fisheries resources in general, and the persistence of sub-stock structuring in particular.